Carboxylated nanocellulose/poly(ethylene oxide) composite films as solid–solid phase-change materials for thermal energy storage. (1st December 2019) - Shi, Zhuqun; Xu, Haiyu; Yang, Quanling; Xiong, Chuanxi; Zhao, Mengchen; Kobayashi, Kayoko; Saito, Tsuguyuki; Isogai, Akira
Graphical abstract: Highlights: TEMPO-CNF/PEO composite films were prepared using water as a medium. The composite film had better optical and mechanical properties than PEO film. The composite films had clear melting and crystallization temperatures. The composite films had extremely low CTE values above the melting point of PEO. The composite films are hopeful solid-solid phase-change materials for energy storage. Abstract: Composite films of poly(ethylene oxide) (PEO) and 0%–20% surface-carboxylated cellulose nanofibrils (CNFs) were prepared by mixing the aqueous CNF dispersion and aqueous PEO solution at various weight ratios followed by casting and drying. The 20% CNF/PEO composite film was transparent, whereas the 100% PEO film was translucent. The addition of CNFs to the PEO matrix resulted in decreases of the crystallinity and crystal size of spherical PEO. The Young's modulus and tensile strength of the 100% PEO film were 0.2 GPa and 6.1 MPa, respectively, and remarkably increased to 2.4 GPa and 86 MPa, respectively, with the addition of 20% CNF. The CNF/PEO composite films had clear melting and crystallization temperatures in the heating and cooling processes, respectively. Nevertheless, the coefficients of thermal expansion at temperatures above the melting point of PEO significantly decreased with the CNF addition. The CNF/PEO composite films are therefore promising solid–solid phase-change materials for energy storage with high film dimensional stability.